2005
DOI: 10.1103/physreve.72.066310
|View full text |Cite
|
Sign up to set email alerts
|

Properties of luminescence from laser-created bubbles in pressurized water

Abstract: The properties of the luminescence pulse from collapsing laser-created bubbles in pressurized water are studied for pressures between 0.25 and 15 bars. The duration of the light pulse is found to be linear in the maximum bubble size, but for a given bubble size it increases with the applied pressure p as p0.38. The number of photons emitted increases quadratically with the bubble size, and increases approximately linearly with pressure. The spectrum of the luminescence is blackbody in form, with a temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 14 publications
4
47
4
Order By: Relevance
“…The usable spectral range of the photodiode is 320-1100 nm. An analysis of the optical spectra given in the literature showed that the maximum temperatures in spark-generated and laser-generated bubbles range 5800-8150 K [5,11,15,18]. Then, using the Wien and Planck Law, it can be verified that the spectral maxima of the optical radiation are within the photodiode bandpass, and that the prevailing part of the radiation is received by the detector.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The usable spectral range of the photodiode is 320-1100 nm. An analysis of the optical spectra given in the literature showed that the maximum temperatures in spark-generated and laser-generated bubbles range 5800-8150 K [5,11,15,18]. Then, using the Wien and Planck Law, it can be verified that the spectral maxima of the optical radiation are within the photodiode bandpass, and that the prevailing part of the radiation is received by the detector.…”
Section: Methodsmentioning
confidence: 99%
“…Using Wien's Law, it can be calculated that the temperatures Θ M 1 ranged 6600-7700 K. Unfortunately, the sizes of the bubbles generated in these experiments are not available. Golubnichii et al [5] studied bubbles generated by an exploding wire technique, and found that the maximum in the spectrum of the optical radiation associated with the first optical pulse u 1 (t) lies approximately [5] (Go), [12] (Ba), [14] (BW), [15] (Br); these values are discussed at the end of this section. vol.…”
Section: No /mentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several observations of the production of light from laser-induced cavitation bubbles collapsing in water [79][80][81][82]. An estimate of the interior bubble temperature at the moment of light emission can be obtained by fitting the spectra to a blackbody form, and in general this yields results of about 8000 K. An extension of these studies to investigate the effect of viscoelastic properties of the liquid surrounding the bubble on the characteristics of the luminescence is highly desirable for a better understanding of the cavitation phenomenon in non-Newtonian fluids and associated damage to nearby boundaries.…”
Section: Outlook and Challengesmentioning
confidence: 99%